Effect of Testing Rate on Adhesion Properties of Acrylonitrile-Butadiene Rubber/Standard Malaysian Rubber Blend-Based Pressure-Sensitive Adhesive - Poh, B. T.; Lamaming, Junidah (Hindawi Publishing Corporation, 2013)
The dependence of loop tack, peel strength, and shear strength of NBR/SMR L blend-based pressure-sensitive adhesives on the rate of testing was investigated using coumarone-indene resin and toluene as the tackifier and solvent, respectively. A 40% NBR content in the NBR/SMR L blend was used throughout the experiment.The adhesion properties weremeasured by a Lloyd Adhesion Tester operating at different rates of testing. The result indicates that loop tack, peels strength, and shear strength increase with the rate of testing due to the viscoelastic response of the adhesive. At low testing rate, the failure mode is cohesive in nature whereas adhesion failure mode occurs at higher testing rates. Adhesion properties also increase with the increase in adhesive coating thickness, an observation which is attributed to the wettability of the adhesive and viscoelastic behavior of the rubber blend.